DAYA GUNA ONDANSENTRON 8 MG IV DIBANDING DENGAN PETHIDIN 0.4 MG/KGBB IV UNTUK MENCEGAH SHIVERING PASCA ANESTESI SPINAL PADA SEKSIO SESARIA - , FERIANTO ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Shivering is an unpleasant yet frequently happened complication after spinal anesthesia. Numerous pharmacological interventions have been studied, but their effectiveness in order to prevent shivering remains unclear and relatively have plenty side effects. Especially pethidine, which has nausea and vomiting side effects. This study purposed on comparing the effect of ondansetron 8 mg and pethidin 0.4 mg/kgBW intravenously as an shivering prevention post spinal anesthesia in caesarean section. Randomized double blind controlled study has been used with the study subjects were 96 pregnant women, age ranged from 18 to 40 years old, ASA I-II physical statues, 37-42 weeks of pregnancy, weight ranged from 40 to 70 kg (BMI < 30 kg/m2), and height > 145 cm who underwent cesarean section under spinal anesthesia. The exclusion criteria were patient/familyâs refusal in research participation, history allergy to bupivacaine, ondansetron, and pethidine, and patient who had been known having congenital disease before, in hypo or hyperthermia conditions, high risk pregnant (such as pre-eclampsia, eclampsia and HELLP syndrome), and pregnant women with heart disease (Hypertension, heart troublesome, heart valves disorders). The drop out criteria were when patients with total spinal, the expected sensoric and motoric block (T4-T8) did not happened after 15 minutes injection, failed spinal anesthesia, participation cancelation, and bleeding complication (such as atonia uteri). This study have been done in patients who underwent caesarean section procedure applied with spinal anesthesia in Dr. Sarjito Hospital Yogyakarta and other educational affiliation hospital consist of Dr. Soeradji Hospital Klaten, Banyumas County Hospital, and Panembahan Senopati County Hospital, Bantul. The study was completed in 4 months started from the end of February into June. The subjects were 96 patient who divided into two groups, which O Group received 8 mg ondansteron intravenously and P Group received 0.4 mg/kgBW intravenous pethidine. The study resulted that shivering incidency was lower in the group who received 8 mg ondansteron intravenously (2 patients) (4,2%) instead of the group who received 0.4 mg/kgBW intravenous pethidine (6 patients). But there was no significant difference statistically, with p<0,05 (p= 0,140). The nauseous side effect was significantly lower in the group who received 8 mg ondansteron intravenously (2 patients) (4,2%) instead of the group who received 0.4 mg/kgBW intravenous pethidine (8 patients) (16,7%) with p < 0,05 (p = 0,045)